Kajian Keterkaitan antara Nutrisi, Hormon, dan Perkembangan Akar Tanaman (Sebuah Review) - Devi Armita (Prosiding Seminar Biologi, 2019)
Root is a vegetative organ that plays a role in the absorption of water and nutrients in the soil or growth media in plants. Therefore the organ which is directly affected by changes in soil conditions is the root. Nutrient supply can influence root development both directly as an external signal and indirectly through changes in internal nutrition. Changes in internal nutrition will be a signal in changes in the distribution of hormones in plants which will eventually cause changes in root morphology. Several studies have reported relationship between the availability of nutrients in the soil and the level of hormones present in plants with the end result of changes in root development and morphology, especially the relationship between nitrogen and some endogenous hormones that play a role in root growth and development in plants, including auxin, cytokinins and abscisic acid (ABA). Deficiency or excess conditions affect the levels of auxin, cytokinins and ABA and affect auxin transport. Different nitrogen fertilizers, NO3- and NH4+ produce different responses in plants to influence root growth and development.